2015
DOI: 10.1002/ejic.201500765
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium(II) and Iridium(III) Complexes Bearing Phosphinepyridonate and Phosphinequinolinolate Chelates

Abstract: International audienceStraightforward preparation of five-membered P,N and P,O prochelates was easily achieved from 6-methyl-2-pyridinol and 2-quinolinol. From these ligands, access to the corresponding well-defined ruthenium(II) and iridium(III) complexes was investigated. Owing to the hemilability as well as the reversible proton-responsive character of these chelates, the resulting well-defined ruthenium complexes exhibit interesting activities in hydrogenatio

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 79 publications
(20 reference statements)
0
9
0
Order By: Relevance
“…Our group recently disclosed a series of new proton responsive bi- and tridentate phosphine pyridon-e/-ate ligands. The corresponding transition metal complexes have shown impressive reactivity for alcohol dehydrogenation and selective formation of acetals or esters . Observing the efficiency of Ru-1 in dehydrogenative coupling of primary alcohols, we envisaged the formation of a corresponding α-alkylated ketone when a secondary alcohol is introduced in the system via dehydrogenative cross-coupling of the two alcohols (Scheme ).…”
mentioning
confidence: 85%
“…Our group recently disclosed a series of new proton responsive bi- and tridentate phosphine pyridon-e/-ate ligands. The corresponding transition metal complexes have shown impressive reactivity for alcohol dehydrogenation and selective formation of acetals or esters . Observing the efficiency of Ru-1 in dehydrogenative coupling of primary alcohols, we envisaged the formation of a corresponding α-alkylated ketone when a secondary alcohol is introduced in the system via dehydrogenative cross-coupling of the two alcohols (Scheme ).…”
mentioning
confidence: 85%
“…[1a], The majority of reports employs simple unsubstituted 2‐hydroxypyridine, 6,6′‐dihydroxy‐2,2′‐bipyridine or 2,9‐dihydroxyphenanthroline, coordinated by iridium. A recent example with a slightly more complex ligand architecture, 2‐hydroxy‐6‐methyl(diphenylphosphino)pyridine, was reported by Achard et al To the best of our knowledge, all reported work relating to cooperative iridium–pyridone catalysis involves iridium(III) metal centres. Rauchfuss has reported the reaction of Cp*Ir(κ 2 ‐2‐pyridonate)Cl with dihydrogen and hydrogen donors .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Achard and co-workers found a κ 2 -P,N coordination mode for the complex resulting from the same metal precursor with the analogous (6-Ph 2 PCH 2 )(2-hydroxy)pyridine ligand. 8 In this case, the ligand was found to be in the hydroxypyridine form, and the bidentate coordination resulted in the removal of one of the chloride ligands from the coordination sphere to form the cationic complex. It should be noted that the utilization of polar solvent methanol may have influenced this selectivity.…”
Section: ■ Results and Discussionmentioning
confidence: 93%
“…The crystal structure of [ 2 ] OTf (Figure , left) shows that the cation adopts a three-legged piano stool complex containing the neutral 6-D i PPin ligand (in the 2-hydroxypyridine form) coordinated via the phosphorus (L) and nitrogen (L) atoms with a κ 2 - P,N coordination mode. The ruthenium center in the cations contains Ru–P, Ru–N, and Ru–Cl bond distances that are comparable to those of the related structures, [RuCl( p -cymene)(κ 2 - P,N -{(6-Ph 2 PCH 2 )(2-hydroxy)pyridine})]Cl and [RuCl(benzene)(κ 2 - P,N -{(6-Ph 2 PCH 2 CH 2 )(2-hydroxy)pyridine})]PF 6 , which both contain a 2-hydroxypyridinephosphine ligand with a κ 2 - P,N coordination mode. , These two latter complexes differ from [ 2 ] OTf in the size of the rings formed upon chelation, which are five- and six-membered chelates, respectively. As expected, however, the N1–Ru1–P1 angles around the ruthenium centers in [ 2 ] OTf are reduced significantly to 67.60(4)° and 67.16(4)° (two angles since there are two independent complexes in the asymmetric unit) due to the strained four-membered ring formed upon chelation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation